Enhancing EFL Students' Writing Proficiency Through HelloTalk: A Qualitative Exploration of Technology-Assisted Language Learning - Hikma Hikma; Sultan Baa (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study examines the use of the HelloTalk application in enhancing English writing skills among EFL students. Employing a qualitative descriptive research design, data were collected through direct observations of four undergraduate participants who had actively used HelloTalk for several months. The findings reveal that HelloTalk provides a dynamic and interactive platform for developing writing skills. Key features such as AI-assisted grammar corrections, vocabulary-building tools, and real-time feedback from native speakers significantly contribute to improving grammatical accuracy, enriching vocabulary, and fostering coherence in written communication. Additionally, the social networking aspects of HelloTalk encourage authentic language interactions, boosting students' confidence and engagement in writing practice. Despite some limitations, the study highlights HelloTalk's potential as a supplementary tool in EFL education. The app's ability to blend formal learning tools with social interaction features makes it an effective resource for creating an immersive and supportive language learning environment. The research underscores the importance of integrating technology, such as HelloTalk, into EFL curricula to optimize students’ writing development. Recommendations include providing structured activities and training educators and learners to maximize the app’s functionalities. This study contributes to the growing discourse on technology-enhanced language learning and offers valuable insights for educators and curriculum developers.